dy/dx = y(xy3-1)=> dy/dx = xy4-y=> dy/dx + y = xy4Dividing the above equation by y3 to get -
y-4 (dy/dx) + y-3 = x ---- A
Put y-3 = t ,then -3y-4 (dy/dx)=(dt/dx) => y-4(dy/dx) = (-1/3) (dt/dx) Substituting above in equation A to get -(-1/3) (dt/dx) + t = x Multiplying both sides by -3=> dt/dx +(-3)t = -3xThe above resides as a linear first order equation of the form-t'+P(x)t=Q(x), where P(x)=-3 and Q(x)=-3xSo, the integrating factor for above bernoulli equation is - M(x)=exp("\\int"-3 dx) = e-3x.Multiplying this by both sides of the equation - e-3x t' + (-3)t e-3x =-3x e-3xAs left hand side represents d/dx(t e-3x) :d/dx(t e-3x) = -3xe-3xIntegrating both sides with respect to x :"\\int"d/dx(t e-3x) dx = "\\int" -3xe-3x dx=> t e-3x = (-3) [ x"\\int"e-3x dx - "\\int" {{(d/dx) x} "\\int"e-3x dx} ]"\\implies"te-3x = (-3) [ (-1/3) x e-3x - "\\int"1. (-1/3) e-3x dx ]"\\implies"t e-3x = x e-3x + (-1/3) e-3x"\\implies"t = x -(1/3) Put t = y-3 to get - y-3 = x - (1/3)
Comments
Leave a comment